Canada in NATO: The Perceptions of a Middle Power in Alliance - Sokolsky, Joel J. (Tufts Archival Research Center, 2005)
Volume 4, Issue 2. Summer Within the NATO alliance Canada has long held an ambiguous position. Although its security is not directly threatened by the Soviet Union, Canada has chosen to adhere to an anti-Soviet military alliance. Joel Sokolsky here outlines the ups and downs of Canadaï¿½s NATO participation over the years and points out the underlying reasons for its continuing membership.